The switch - Horowitz, Anthony (Puffin Books New York, 2014)
Tad Spencer lives a life of luxury: a mansion, servants, exotic vacations, and all the toys he could dream of. But when his father denies him a trip to a theme park, Tad wishes he were someone else. The next day, he wakes up as Bob Snarby, a carnival worker living in abject conditions in a criminal world. This terrifying body swap is just the beginning of an adventure that will lead Tad to uncover a secret that will change his life forever